Traditions and future, a monument, the International Symposium XVIII edition from 6 to 9 october 2016 - Iaşi (Confluenţe Bibliologice, 2025)
MONUMENT symposium existed for 18 years in Iasi and is coordinated with professionalism by dr. Aurica Ichim, who also is the head of the Union Museum in Iasi. It is sponsored by cultural institutions in the country, Moldova and Ukraine: the Ministry of Culture of Romania, the Moldova National Museum Complex in  Iasi - Union Museum, Metropolitan of Moldova and Bucovina, the National Union of Restorers of Historic Monuments, Academy of Sciences of Moldova, Romanian Cultural Centre ,,Eudoxiu Hurmuzachi” from Chernivtsi.
Keywords: dissemination of information